2021
DOI: 10.3390/su13041981
|View full text |Cite
|
Sign up to set email alerts
|

European Green Deal: Environmental Taxation and Its Sustainability in Conditions of High Levels of Corruption

Abstract: Despite environmental taxation’s presumed advantages for long-term sustainable development goals, the problematic institutional conditions associated with high levels of corruption could become a significant obstacle undermining these efforts. Taking the example of the Czech Republic as a benchmark, the aim of this article is to evaluate the impact of corruption and its implications on the size of the official and the shadow economy in the sector burdened with environmental excise tax while confronting it with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Empirical studies found that a decrease in corruption affects carbon emissions in the short term while a long-run effect is insignificant [58,59]. [60] reported the limiting impact of corruption on sustainable policy implementations. Similarly, corruption jeopardizes the green environment policy in European countries [61].…”
Section: Review Of Past Studiesmentioning
confidence: 99%
“…Empirical studies found that a decrease in corruption affects carbon emissions in the short term while a long-run effect is insignificant [58,59]. [60] reported the limiting impact of corruption on sustainable policy implementations. Similarly, corruption jeopardizes the green environment policy in European countries [61].…”
Section: Review Of Past Studiesmentioning
confidence: 99%
“…This collaboration may be realized through participation in the EU's industrial alliances and related decentralized EU institutions. An inclusive stakeholder participation strategy is essential to ensuring societal acceptability and widespread support for the green revolution [105][106][107].…”
Section: Literaturementioning
confidence: 99%
“…Wang et al [11] found out that the elasticity of the price of demand in the cement market in China is so great that the tax on the environment imposed on the cement industry shows, a negative impact on corporate revenue and profits. Kotl'an et al [12] examine the Green Deal of the European and conclude a high tax on the environment affects negatively economic activities and limits sustainable development policy implementation. Mousavian and others.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%